Modelling Catchments in Qatar to Assist in Operations - Gokhale, Shirish; Gupta, Anil Kumar; Fakhroo, Nasser Yousef; Devang, Kapil; Kelly, Tim (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Qatar is experiencing unprecedented growth and infrastructure is being developed at a rapid pace. The infrastructure is served by storm water systems which are under development and need to be resilient in case of storms. The storm water systems serving Doha and nearby areas are complex in nature. They include passive, positive drainage systems and also connect critical locations such as underpasses and a number of ancillaries. The two main reasons adding to the complexity are asset creation work ongoing at multiple locations and various temporary and permanent systems operating simultaneously. A standardized approach for operating this complex storm drainage network becomes essential. Also, while solving problems such as flooding during a rainfall event, at times root cause of a problem may be at a different geographical place than that of the actual location of the problem. It is difficult to arrive at a root cause without an overall understanding of the system. This along with a standardized approach is useful in taking better informed decisions before, during and after storm events. A coordinated effort between Ashghal Design and Operation & Maintenance Departments resulted into an operational philosophy. Hydraulic modelling supported by comprehensive GIS information played an important role in developing this. The work consisted of considering issues encountered during recent major storm events and simulating multiple scenarios. The recommended actions are currently under implementation. The next stage will be to set up a near real time operation system which would include SCADA data linked to and hydraulic models.